Efficient involvement of human resources in innovations through effective communication - Stachova, Katarína; Stacho, Zdenko; Vicen, Vlastimil (Business: Theory and Practice, 2017)
Systematic creation and use of human potential enables building and development of strengths of organisations. If organisations can fully use the potential of their employees it will affect their ability to succeed in competitive environment. Our paper focuses on open and broad communication, as it has a significant impact on both formal and informal labour relations, which, along with information share and knowledge continuity, essentially affect team creation. The questionnaire survey focused on finding out whether and to what extent organisations operating in Slovakia focus on communication. The paper also provides a simple method of evaluating the level of communication and engagement of employees in problem solving in companies. This method is a simple instrument enabling the conduction of analysis in a short time interval, while analysing employees are able to identify a current level of their company on the grounds of results, as well as they are able to identify bottlenecks preventing them in innovation potential increase.